2019
DOI: 10.1177/0886260519888532
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Victimization, Social Support, and Resilience: Effects on the Anxiety Levels of Young Mothers

Abstract: Young mothers face considerable challenges that can affect their mental health, with anxiety being one of the most common mental health problems observed in this population. Furthermore, pregnancy is one of the risk factors for intimate partner violence (IPV). There is thus an urgent need to explore the IPV risk faced by young mothers and its association with their mental health, anxiety in particular. The study aimed to investigate the correlation between IPV victimization and anxiety in young mothers, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 76 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…A large proportion of included nursing studies from Hong Kong and Taiwan involved researchers from non-nursing disciplines; at least in Hong Kong, a nursing researcher led the multidisciplinary team. Nursing researchers were also identified in studies led by non-nursing researchers from social work and primary care [136] , [137] , [138] . Studies from Hong Kong also involved collaborations with non-government organisation (NGO) like Hong Kong SKH Lady MacLehose Centre [94] .…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of included nursing studies from Hong Kong and Taiwan involved researchers from non-nursing disciplines; at least in Hong Kong, a nursing researcher led the multidisciplinary team. Nursing researchers were also identified in studies led by non-nursing researchers from social work and primary care [136] , [137] , [138] . Studies from Hong Kong also involved collaborations with non-government organisation (NGO) like Hong Kong SKH Lady MacLehose Centre [94] .…”
Section: Discussionmentioning
confidence: 99%
“…In a study developed in Japan with participants who suffered psychological violence from intimate partners, anxiety symptoms were the main exposure to violence. The chances of having anxiety as an outcome of the aggression were almost five times greater in women exposed to violence (Choi et al., 2019). In another study, childhood trauma (physical and sexual abuse) made obesity and depressive symptoms in adulthood three times more common among exposed persons.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the correlates of resilience and psychological health, research has shown that higher resilience is positively correlated with psychological health and negatively correlated with anxiety-depression and post-traumatic stress symptoms. Choi et al (2019) noted that resilience did not predict generalized anxiety scores when controlling for variability in the heterogeneity of women's past victimization. The au- thors posited that this was because economic and employment stability, social support, and the history of abuse had a stronger effect than resilience on the anxiety levels of their sample given the participants' characteristics (young women with children).…”
Section: Correlates Of Resilience In Women Survivors Of Ipvmentioning
confidence: 98%